ABOUT COMPATIBILITY OF THE VEKUA EQUATION WITH SOME OTHER EQUATIONS - Brsakoska, Slagjana (Matematichki Bilten, 2014)
In the paper, the compatibility of the Vekua equation with equations that define some generalized analytical functions will be considered. The main results are formulated in a few theorems.